Morphology, viability, meiotic index and pollen cytochemistry of sangra d'água (Croton urucurana Baill) (Research, Society and Development, 2022)
The sangra d’agua (Croton urucurana Baill) is a tree species, used in traditional medicine and with potential for use in reforestation. Information on reproductive aspects of the species, such as morphology, viability and pollen cytochemistry provide data that can be used in projects aimed at its conservation. This work aimed to use colorimetric tests to evaluate pollen viability, meiotic index and identify the nutrient reserve substances of pollen grains, as well as to characterize the morphology of pollen from bleeds. Flower buds were collected in pre-anthesis from ten individuals located in the municipality of Alta Floresta-MT. For the morphological analysis of pollens, the acetolysis method was used, while for the evaluation of pollen viability, Alexander's reagent and acetic carmine 2% were used, which was also used to estimate the meiotic index. For analysis of reserve substances, lugol 2% and sudan IV were used. Bleeding pollens were classified as spherical of the prolate-spheroidal subtype. All dyes used proved to be efficient in distinguishing between viable and non-viable pollens and also in detecting the reserve substance. The species showed an average of 98.9% for pollen viability and 94.67% for the meiotic index, indicating meiotic regularity. The cytochemical analysis revealed that the species has starch and lipid as reserve substances. The high percentage of viable pollens indicates that the sangra d’água has reproductive stability, being reproductively adapted to the environment where it is naturally found in the municipality of Alta Floresta, MT.